2016
DOI: 10.11157/anzswj-vol25iss2id83
|View full text |Cite
|
Sign up to set email alerts
|

Gendered violence in natural disasters: Learning from New Orleans, Haiti and Christchurch

Abstract: Why are women so vulnerable to violence and death as a result of disaster compared with men? This article investigates how global environmental forces in the form of natural disasters from floods, droughts and famines to earthquakes, tsunamis and hurricanes affect women and men differently. Disasters are known to have direct and indirect impacts on gender-based violence particularly against women and girls, revealing a pattern of heightened violence and vulnerability in their aftermath. These gendered impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 12 publications
0
43
0
Order By: Relevance
“…The challenge of protecting vulnerable women during and after a disaster has surfaced in the literature as early as the late 90s with Enarson's (1999) work with continued investigation presently (First, First and Houston, 2017;Norris, 2014). For example, True (2013) has extended the literature and suggested that gendered violence increases during and after a disaster unless the disaster response community finds ways to address female vulnerability.…”
Section: The Intersection Of Disasters and Domestic Violencementioning
confidence: 99%
“…The challenge of protecting vulnerable women during and after a disaster has surfaced in the literature as early as the late 90s with Enarson's (1999) work with continued investigation presently (First, First and Houston, 2017;Norris, 2014). For example, True (2013) has extended the literature and suggested that gendered violence increases during and after a disaster unless the disaster response community finds ways to address female vulnerability.…”
Section: The Intersection Of Disasters and Domestic Violencementioning
confidence: 99%
“…Instead, as Fionnuala Aoláin (2011) argues, one should look at the existing conditions prior to the disaster because “the specific vulnerabilities identified in the moment of crisis can only be completely understood and fully addressed by reference to the backdrop” (p. 6). Researchers documenting violence against women in disaster settings such as the 2010 earthquake in poverty-stricken Haiti (Le-Ngoc, 2015), the 2004 tsunami in war-torn Sri Lanka (Fisher, 2010), the 2011 Christchurch, New Zealand earthquakes and the 2005 Hurricane Katrina in the United States (True, 2013) also stress the importance of a contextual approach. Preexisting inequalities are likely to be magnified by climate disasters.…”
Section: Gendered Vulnerabilities and Disastersmentioning
confidence: 99%
“…While a combination of factors may trigger violence in disaster situations, this should not be confused with the deeply rooted causes of gendered violence such as sexual stereotyping, women’s socioeconomic disempowerment, and limited social mobility (Fisher, 2010; Horton & Rydstrom, 2011). In recent scholarship on gender and disasters (Enarson & Chakrabarti, 2009; True, 2013), women are not essentialized and victimized as vulnerable as emphasis is put on the social aspects of natural disaster. As Sarah Fisher (2010) observes, “both during disaster and at other times, male perpetrators use violence as a means to assert power and control over women” (p. 913).…”
Section: Gendered Vulnerabilities and Disastersmentioning
confidence: 99%
“…Interestingly, the perception that the earthquakes have altered the social landscape is also communicated through posters shown below as part of the Art Box installation which features commentary on the increasing role of women in the construction industry with the title “Rebuilding Preconceptions” (Figure ). The aim here is not to go into specific detail of the gendered dynamics in the recovery (for example, see Adams‐Hutcheson ; Gordon ; True ); however, these examples demonstrate how community‐led performances and art can contribute to politicising issues that have arisen following the earthquakes.…”
Section: Hope and Possibility Through Community‐led Recoverymentioning
confidence: 99%